2017
DOI: 10.1016/j.ultsonch.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Sono-crystallization kinetics of K2SO4: Estimation of nucleation, growth, breakage and agglomeration kinetics

Abstract: Application of ultrasound in crystallization has showed improved process characteristics. Although several attempts have been made in the past to study the sono-crystallization kinetics, only nucleation and crystal growth were considered, neglecting breakage and agglomeration of crystals. In this study, an attempt is made for the estimation of the kinetic parameters of all the phenomena occurring simultaneously during sono-crystallization. For this, both conventional and ultrasonic crystallization of KSO-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…In turn, this can again be correlated to a decrease in secondary nucleation and disaggregation events. Consequently, less surface area becomes available for the deposition of crystalline material and the desupersaturation progresses more slowly in comparison to an elevated ultrasonic power , .…”
Section: Resultsmentioning
confidence: 64%
“…In turn, this can again be correlated to a decrease in secondary nucleation and disaggregation events. Consequently, less surface area becomes available for the deposition of crystalline material and the desupersaturation progresses more slowly in comparison to an elevated ultrasonic power , .…”
Section: Resultsmentioning
confidence: 64%
“…The preparations are identical to the nucleation temperature experiments described in Section 2.3. The experiment is started by cooling thermostatic bath 1 at a cooling rate of 0.6 • C/min and switching on the ultrasound at a calorimetric power of 8 W. This cooling rate of 0.6 • C/min was selected because the literature showed that ultrasound caused a significant reduction in MZW at cooling rates of 0.5-0.7 • C/min, while this effect was negligible for higher cooling rates of 2 • C/min [25,33]. The moment crystals were detected, the solution was transferred to the batch vessel by switching the 3-way valve towards the batch vessel.…”
Section: Experimental Procedures Batch Growthmentioning
confidence: 99%
“…Several studies have been devoted to the crystallization process of K 2 SO 4 in the aqueous solution. [ 8,13–19 ] Nývlt and Hostomská [ 13 ] indicated that the metastable zone width of K 2 SO 4 aqueous solution decreased with increasing the value of pH and pH also affected the solution structure. Kobari et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bari et al. [ 19 ] found that the reduction in the induction time, reduction in metastable zone width, and narrowing of crystal size distribution were the key observations of K 2 SO 4 sono‐crystallization experiments.…”
Section: Introductionmentioning
confidence: 99%